Identification of PMD subgroups using a myelination score for PMD. (November 2022) - Harting, Inga; Garbade, Sven F.; Rosendaal, Stefan D.; Mohr, Alexander; Sherbini, Omar; Vanderver, Adeline; Wolf, Nicole I.
Abstract: Background: The clinical spectrum of Pelizaeus-Merzbacher disease (PMD), a common hypomyelinating leukodystrophy, ranges between severe neonatal onset and a relatively stable presentation with later onset and mainly lower limb spasticity. In view of emerging treatment options and in order to grade severity and progression, we developed a PMD myelination score. Methods: Myelination was scored in 15 anatomic sites (items) on conventional T2-and T1w images in controls (n = 328) and 28 PMD patients (53 MRI; n = 5 connatal, n = 3 transitional, n = 10 classic, n = 3 intermediate, n = 2 PLP0, n = 3 SPG2, n = 2 female). Items included in the score were selected based on interrater variability, practicability of scoring and importance of scoring items for discrimination between patients and controls and between patient subgroups. Bicaudate ratio, maximal sagittal pons diameter, and visual assessment of midsagittal corpus callosum were separately recorded. Results: The resulting myelination score consisting of 8 T2-and 5 T1-items differentiates patients and controls as well as patient subgroups at first MRI. There was very little myelin and early loss in severely affected connatal and transitional patients, more, though still severely deficient myelin in classic PMD, ongoing myelination during childhood in classic and intermediate PMD. Atrophy, present in 50% of patients, increased with age at imaging. Conclusions: The proposed myelination score allows stratification of PMD patients and standardized assessment of follow-up. Loss of myelin in severely affected and PLP0 patients and progressing myelination in classic and intermediate PMD must be considered when evaluating treatment efficacy. Highlights: Routine MR images, used retrospectively, allowed to differentiate PMD subtypes and document changes in myelination. Classic and intermediate PMD show ongoing myelination during childhood. Severely affected patients show very little myelin and early loss of myelin signal. Atrophy was present in 50% of patients and increased with age at imaging.